Penerapan Pembelajaran Problem Based Learning Dengan Prinsip Understanding By Desain Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Matematika - I Made Surat; Ni Komang Diva Treesyayanthi Wahada (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
Students' mathematics learning outcomes are relatively low in Mathematics subjects. The aim of this research is to improve student learning outcomes with the Problem Based Learning learning model. PBL is carried out by applying the principles of Understanding by Design (UbD). Each cycle consists of planning, implementation, observation and reflection. This research was carried out in class VII C of SMP 8 Denpasar with 41 students as subjects. This research uses test and non-test instruments in the form of student learning outcomes tests and interviews. The results of the research carried out were that in Cycle I the percentage of students who completed was 48.78%, then in Cycle II the percentage of completion was 78.05%, because the students' grades had met the specified classical completeness so the research was stopped in Cycle II. Based on these results, it can be concluded that there has been an increase in student learning outcomes in Mathematics learning by implementing PBL with the principle of UBD.